Lipophilicity prediction of three photosensitizers by liquid–liquid extraction, HPLC, and DFT methods. (2nd August 2022) - Myrzakhmetov, Bauyrzhan; Honorien, Jonathan; Arnoux, Philippe; Fournet, René; Tsoy, Irina; Frochot, Céline
Abstract: Photodynamic therapy (PDT) is a method of treating precancerous diseases and malignant neoplasms. The efficacy of PDT depends on different parameters such as light dosimetry, oxygen availability, and photophysical and physical–chemical properties of the photosensitizer. In PDT, a photosensitizer is activated using light to promote oxygen photosensitization and cellular transport plays a key role in the reach of it to the desired tissue. In particular, to know the effectiveness of the drug delivery in PDT and its dosage forms to target damaged organs, along with such characteristics as water solubility, it is important to know the ability of a substance to penetrate through cell membrane or accumulate in it. Lipophilicity is used to quantify the earlier‐described abilities. We evaluated the lipophilicity of three selected photosensitizers (PS) (protoporphyrin IX, pyropheophorbide‐a and photofrin) by means of three different methods: octanol–water distribution methods (shake‐flask), reversed‐phase high‐performance liquid chromatography (HPLC) and theoretical calculations based on density functional theory (DFT). We describe and compare the results of these various methods. Abstract : Photodynamic therapy is a novel cancer treatment based on the selective accumulation of a photosensitizer in a tumor and the subsequent creation in it (under the influence of laser radiation with a certain wavelength) of a photochemical reaction that destroys tumor cells. Lipophilicity (given as the logarithm of the octanol–water distribution coefficient, LogD) becomes a significant factor in this process. Unfortunately, there are no experimental methods for determining the LogD value for photosensitizers such as protoporphyrin IX, pyropheophorbide‐a, and photofrin.